Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Enantioselective synthesis of (+)-(S,S)-reboxetine - Siddiqui, Shafi A.; Narkhede, Umesh C.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synlett, 2006)
An efficient enantioselective synthesis leading directly to (+)-(S,S)-reboxetine has been described from commercially available trans-cinnammyl bromide using Sharpless asymmetric dihydroxylation as the key step.
Keywords: coupling; Dihydroxylation; Hydrogenation; reboxetine; trans-cinnamyl bromide

Ionic liquid promoted facile one-pot synthesis of 1-pyridylimidazo[1,5-a]pyridines from dipyridylketone and aryl aldehydes - Siddiqui, Shafi A.; Potewar, Taterao M.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Synthesis-Stuttgart, 2006)
A highly efficient one-pot methodology has been developed to synthesize a class of substituted 1-pyridylimidazo[ 1,5-a]pyridines, using Bronsted acidic ionic liquid 1-butylimidazolium tetrafluoroborate, [Hbim]BF4 in excellent isolated yields in the absence of any catalyst. The methodology is characterized by simple work-up procedures along with efficient recovery and recycling of the ionic liquid, which acts as a reaction medium as well as a promoter.
Keywords: 5-a]pyridines; Aldehyde; ammonium acetate; heterocycles; imidazo[1; ionic liquids

Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

Efficient synthesis of 2,4-disubstituted thiazoles using ionic liquid under ambient conditions: a practical approach towards the synthesis of Fanetizole - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2007)
A highly efficient and rapid synthesis of 2-amino-4-arylthiazoles and 2-methyl-4-arylthiazole from alpha-bromoketone and thiourea/thioamide is described using room temperature ionic liquid at ambient conditions. The method is simple, rapid and practical, generating thiazole derivatives in excellent isolated yields. This protocol is utilized for a commercially feasible synthesis of an anti-inflammatory agent, Fanetizole. (c) 2007 Published by Elsevier Ltd.
Keywords: alpha-bromo ketone; ionic liquids; thiazoles; thiourea/thioamide

Enantioselective synthesis of (S)-dapoxetine - Siddiqui, Shafi A.; Srinivasan, Kumar V. (Tetrahedron-Asymmetry, 2007)
An efficient enantioselective synthesis leading directly to (+)-(S)-dapoxetine has been described for the first time using Sharpless asymmetric dihydroxylation, Barton-McCombie deoxygention, and Mitsunobu reaction as the key steps. (C) 2007 Published by Elsevier Ltd.

Novel one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in water - Palimkar, Sanjay S.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Green Chemistry, 2007)
A novel green and efficient one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in excellent isolated yields has been reported. The methodology initially involves the formation of ynones via coupling of a wide range of acid chlorides with terminal alkynes catalysed by Pd(OAc)(2) under copper-, ligand- and solvent-free conditions in just 10 min at rt followed by the Michael addition and cyclocondensation of o-phenylenediamines added in situ using water as a solvent at reflux temprature. In addition, the structure of the benzodiazepine was confirmed to be the diimino molecule and not the enamine by X-ray crystallographic analysis of the benzodiazepine 4b. The methodology is suitable for the operation in combi-chem mode to generate libraries of a diverse array of benzodiazepines. The methodology has been successful in achieving the twin green chemistry objectives of a solvent and ligand free operation and the use of water as a non-hazardous, inexpensive and readily available solvent in the sequential reaction steps performed in situ, thus combining the features of both economic and environmental advantages.

Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition

Synthesis of an indole containing KDR kinase inhibitor by tandem Sonogashira coupling-5-endo-dig-cyclization as a key step - Palimkar, Sanjay S.; More, Vijaykumar S.; Kumar, P. Harish; Srinivasan, Kumar V. (Tetrahedron, 2007)
An efficient synthesis of the potent KDR kinase inhibitor 3-[5-[[4-(methylsulfonyl)-1-piperazinyl]methyl]-1H-indol-2-yl]quin oline-2-(1H)-one using a Sonogashira coupling-5-eiido-dig-cyclization strategy is described. (c) 2007 Elsevier Ltd. All rights reserved.

Catalyst-free efficient synthesis of 2-aminothiazoles in water at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Tetrahedron, 2008)
A highly efficient and facile method has been described for the synthesis of substituted 2-aminothiazoles in water without any added catalyst or co-organic solvent. The reaction was carried out at ambient temperature and the products were obtained in excellent isolated yields. The developed protocol is successfully applied for the preparation of an anti-inflammatory drug, fanetizole. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-aminothiazoles; ambient temperature; environment-friendly synthesis; Water

Efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in an ionic liquid/water system under ambient conditions - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient and eco-friendly synthesis of 2-amino-1,3-selenazoles in ionic liquid/water solvent system is described. The paper describes synthesis of 2-amino-1,3-selenazoles by condensation of various phenacyl bromide with selenourea under ambient conditions in short reaction times. This protocol has notable advantages such as the absence of any added catalyst, simple operation and excellent yields of products and recyclability of the ionic liquid.
Keywords: 2-Amino-1; 3-selenazoles; ambient conditions; heterocycles; ionic liquid/water system; selenoureas; substituted phenacyl bromide

Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling

Efficient synthesis of quinoxalines in the ionic liquid 1-n-butylimidazolium tetrafluoroborate ([Hbim]BF4) at ambient temperature - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Quinoxaline derivatives have been synthesized in excellent yields using an ionic liquid (IL) (viz., 1-n-butylimidazolium tetrafluoroborate) as a reaction medium as well as promoter from various 1,2-diketones and aryl-1,2-diamines. The process is general for the synthesis of quinoxaline derivatives from aromatic as well as aliphatic-1,2-diketones. The advantages of the present method are ambient reaction temperature, simplicity of operation, high yields of products, the recyclability of the IL, and ecofriendly nature of the reaction medium.
Keywords: 1; 2-diamines; 2-Diketones; Aryl-1; ionicliquid(IL); quinoxalines

Novel process for the synthesis of class I antiarrhythmic agent (+/-)-cibenzoline and its analogs - Gholap, Atul R.; Paul, Vincent; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Synthesis of (+/-)-cibenzoline and its analogs has been achieved by a simple sequence of reactions. The diaryl cyanoolefin intermediate 3 could be prepared by Knoevenagel condensation of benzophenone with ethylcyanoacetate to form the tetra-substituted olefin intermediate 2 followed by Krapcho deethoxycarbonylation or from beta-hydroxynitrile intermediate 2' followed by the elimination of hydroxyl group respectively. The 2,2-diphenylcyclopropanecarbonitrile 4 was synthesized from intermediate 3 by cyclopropanation, which was converted to (+/-)-2-(2,2-diphenylcyclopropyl)-2-imidazoline 5 by reaction with ethylenediamine in the presence of a catalytic amount of sulfur. Moreover, the obtained 2-imidazolines were smoothly oxidized to the corresponding imidazoles 6 in good to moderate yields.
Keywords: Benzophenone; cibenzoline; cyclopropanation; diaryl cyanoolefin

Simple and efficient one-pot, three-component, solvent-free synthesis of beta-enaminones via sonogashira coupling-Michael addition sequences - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
A simple, efficient, and environmentally friendly one-pot, three-component synthesis of beta-enaminones via Sonogashira coupling-Michael addition sequences under solvent-free conditions has been reported. Also the synthesis of beta-enaminones has been achieved in high yields by the direct reaction of amines with ynones under solvent-free conditions.
Keywords: Alkynes; beta-enaminones; coupling; Michael additions; solvent free; ynones

Synthesis of tryptanthrin and deoxyvasicinone by a regioselective lithiation-intramolecular electrophilic reaction approach - Potewar, Taterao M.; Ingale, Sachin A.; Srinivasan, Kumar V. (Arkivoc, 2008)
An efficient synthesis of the 4(3H)-quinazolinone-based alkaloids, tryptanthrin and deoxyvasicinone has been achieved in good overall yields by using the strategy of regioselective lithiation-intramolecular electrophilic reaction as a key-step. Both the molecules have been synthesized in just two-steps from readily available starting materials.
Keywords: 4(3H)-Quinazolinone heterocycles; deoxyvasicinone; lithiation-intramolecular electrophilic reaction; tryptanthrin

Ultrasound promoted copper-, ligand- and amine-free synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Ultrasonics Sonochemistry, 2008)
This method describes the results of the optimized conditions for the one-pot synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization under ultrasonic irradiation at ambient temperature in the absence of copper, ligand and amine. The protocol tolerates wide range of functional groups present in both the coupling components, especially base labile nitro group was not affected under these mild conditions giving excellent yields of the nitro benzo[b]furans. The formation of Pd(0) nanoparticles as the active species has been shown by TEM analysis and the unique role of ultrasound in promoting the total sonochemical protocol has been substantiated by way of control experiments. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: 1-alkynes; benzo[b]furans; Sonogashira coupling-5-endo-dig-cyclization

Proline-catalyzed simple and efficient synthesis of 1,8-dioxo-decahydroacridines in aqueous ethanol medium - Venkatesan, K.; Pujari, Suresh S.; Srinivasan, Kumar V. (Synthetic Communications, 2009)
Proline-catalyzed synthesis of 1,8-dioxo-decahydroacridines is achieved via one-pot, three-component condensation of aromatic aldehydes, cyclic diketone, and aryl amines in aqueous ethanol medium. This method offers the advantages of proceeding in neutral and mild conditions, giving high to excellent yields of acridines with easy workup procedure.
Keywords: 1; 8-dioxodecahydroacridines; aqueous media; one-pot MCR; Proline